Pharmacokinetics and Pharmacodynamics of the Plant Sarsabil Prepared on the Basis of Phytoactive and Extract of High Effectiveness in The Practice of Aesthetic Medicine Dermatology and Dermatocosmetalology Analysis of Theoretical and Practical Goals (Texas Journal of Agriculture and Biological Sciences, 2023)
In medical practice, more than 100 folk remedies use about 600 medicinal plants and their various forms (infusion, decoction, tincture, dry and liquid extract, powder, tablet, solution for injection and other phytopreparations. Their pharmacological effects according to various, these medicinal plants and their phytopreparations are distributed in therapeutic doses to the symptoms of the disease. The healing effect of medicinal plants depends on their biologically active substances. The chemical structure of these substances is different, and they have different pharmacological effects. In the medicinal plant, biologically active substances are formed in the first and second processes, in the first one, proteins, lipids, carbohydrates, enzymes and vitamins are synthesized, and in the second one, alkaloids, glycosides, active compounds, essential oils, additives, pectins, coumarins, including phytoncides and others. In addition to these, the plant contains biologically active and pharmacologically indifferent substances